1983
DOI: 10.1002/hlca.19830660406
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyphenyl‐1‐methylpyridinium‐jodide als potentielle Reaktivatoren von mit Organophosphor‐Verbindungen vergifteten Acetylcholinesterasen

Abstract: Hydroxyphenyl-1-methylpyridinium-iodide as Potential Reactivators of Acetylcholinesterase Poisoned with Organophosphoms Compounds. HELVETICA CHIMICA ACTA -Vol. 66, Fax. 4 (1 983) -Nr. 103 Schema 6 . Resonanzstabilisiertes Phenolat-ion c _

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The physical and spectral data are analogous to those previously described. 27 2-(2-Methoxyphenyl)pyridine (3c). 26 The procedure is as described for 2a but using 2-fluoropyridine (87 µL, 97 mg, 1.0 mmol) instead of 3-fluoropyridine, 2-methoxyphenylmagnesium bromide (1.2 mmol) in THF (1.2 mL) instead of PhMgCl, and Ni(acac) 2 (13 mg, 50 µmol) and dppp (21 mg, 50 µmol) instead of NiCl2(dppe): yield 79% (eluent CH2Cl2/Et2O, 95:5); 1 H NMR (CDCl3) δ 3.87 (s, 3H), 7.02 (d, 1H, J ) 8.3 Hz), 7.09 (t, 1H, J ) 7.5 Hz), 7.2 (m, 1H), 7.37 (td, 1H, J ) 7.8, 1.7 Hz), 7.7 (m, 3H), 8.71 (dd, 1H, J ) 4.3, 1.2 Hz); 13 C NMR (CDCl3) δ 56.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and spectral data are analogous to those previously described. 27 2-(2-Methoxyphenyl)pyridine (3c). 26 The procedure is as described for 2a but using 2-fluoropyridine (87 µL, 97 mg, 1.0 mmol) instead of 3-fluoropyridine, 2-methoxyphenylmagnesium bromide (1.2 mmol) in THF (1.2 mL) instead of PhMgCl, and Ni(acac) 2 (13 mg, 50 µmol) and dppp (21 mg, 50 µmol) instead of NiCl2(dppe): yield 79% (eluent CH2Cl2/Et2O, 95:5); 1 H NMR (CDCl3) δ 3.87 (s, 3H), 7.02 (d, 1H, J ) 8.3 Hz), 7.09 (t, 1H, J ) 7.5 Hz), 7.2 (m, 1H), 7.37 (td, 1H, J ) 7.8, 1.7 Hz), 7.7 (m, 3H), 8.71 (dd, 1H, J ) 4.3, 1.2 Hz); 13 C NMR (CDCl3) δ 56.…”
Section: Discussionmentioning
confidence: 99%
“…The combined extracts were washed (methyl tert -butyl ether), basified (aqueous NaOH) and extracted with methyl tert -butyl ether (4 × 300 mL). The combined extracts were dried (Na 2 SO 4 ), and the solvent was evaporated off under reduced pressure to yield the crude product which was purified by recrystallisation from methyl tert -butyl ether−cyclohexane to give 8 (50 g, 93%) as a colorless crystalline solid, mp 94−96 °C (lit . 95−96 °C).…”
Section: Methodsmentioning
confidence: 99%
“…To date, significant effort has been dedicated to synthesizing phenol and hydroxylated arenes, as they are the building blocks of many bioactive molecules, pharmaceuticals, polymers, and light-emitting materials. The direct C–H oxidation leading to hydroxylation is an attractive method for generating important phenol products. , In 2009, Yu et al showed carboxylic group directed ortho-hydroxylation of benzoic acids using a Pd-catalyst with 1 atm of O 2 or air . The same group has also explored the Cu­(II)-catalyzed ortho-C–H hydroxylation of aryl C–H bonds .…”
mentioning
confidence: 99%